Evolução tectônica do Trend Badejo-Linguado-Pampo, bacia de Campos (RJ) - Scalvi, Bruno Tambellini [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The regional geological work for the oil industry, in order to find potential areas for hydrocarbon exploration and understand the geological parameters responsible for the formation of the deposit are known importance. This work fits into that scenario, with regional research with the aid of wells and 2D and 3D seismic sold by DBEP (Database Exploration and Production). Were also used as GeoGraphix software package Landmarks modules Prizm and SeisWork 2D and 3D, and the Surfer 8 and ArcGIS 9.2 with the infrastructure provided by the 05 PRH - ANP with LSGI (Laboratory of Seismic and Geological Interpretation) located at UNESP -- Campus de Rio Claro. The work focuses on study the trend of oil-Badejo-Linguado-Pampo, producing fields since the beginning of offshore holdings. The Campos Basin is now known as the offshore basin of the country more productive, and the high structural Badejo is a structure of great importance in the basin presents itself as largely responsible for the conditioning of hydrocarbon fields Pampo, Linguado and Badejo. Therefore this work also aims to increase knowledge of the region in terms of tectonic and stratigraphic characterize the geometry of the structures associated with this major regional structure. For this we used structural contour maps of the main chrono-horizons, and Isopach maps for the purpose of better understanding the tectono-sedimentary evolution of the Campos Basin locally.

Os trabalhos geológicos regionais para a indústria petrolífera, com a finalidade de encontrar áreas potenciais para a exploração de hidrocarbonetos e entender os parâmetros geológicos responsáveis pela formação do depósito são de conhecida importância. A realização deste trabalho se enquadra nesse cenário, com investigação regional feita com auxílio de poços e de sísmica 2D e 3D cedidos pelo BDEP (Banco de Dados de Exploração e Produção). Também foram utilizados softwares como Geographix do pacote Landmarks módulos Prizm e SeisWork 2D e 3D, além do Surfer 8 e Arcgis 9.2 com a infra-estrutura cedida pelo PRH 05 – ANP com o LISG (Laboratório de Interpretação Sísmica e Geológica) situado na UNESP – Campus de Rio Claro. O trabalho tem como foco de estudo o trend petrolífero de Badejo-Linguado-Pampo, campos produtores desde o início das explorações offshore. A Bacia de Campos atualmente é conhecida como a bacia offshore mais produtora do país, e o alto estrutural de Badejo é uma estrutura de grande importância na referida bacia apresentando-se como grande responsável pelo condicionamento de hidrocarboneto nos campos de Pampo, Linguado e Badejo. Portanto este trabalho visa além de aumentar o conhecimento da região em termos tectônicos e estratigráficos, caracterizar a geometria das estruturas associadas a esta importante estrutura regional. Para isso foram utilizados mapas de contorno estruturais dos principais crono-horizontes, bem como mapas de isópacas com a finalidade de melhor entender a evolução tectono-sedimentar da Bacia de Campos localmente.
Keywords: Geologia estrutural; Sedimentação e depósitos; Alto de badejo; Structural geology; Tectonics; Sedimentation; Badejo high